Development of a chain throwing game to improve overhand throwing in softball - Sagita Dwi Rosania; Basuki Basuki; Nurdian Ahmad (Sriwijaya Journal of Sport, 2024)
This research aims to develop a learning model in the form of a chain throwing game using physical products in the form of guidebooks for educators and video tutorials on how to play. The research method used is development research. The sample of this research was 132 students. The research instrument used a questionnaire for 3 validators, and a student questionnaire. The data analysis technique uses quantitative descriptive with percentage score results. The average score obtained from the evaluation results from game experts was 93.33% in the content aspect, 94% in the quality aspect (Very Good), learning material experts were 96.67% in the content aspect, 96% in the quality aspect, and 96% in the language aspect. 93.33% (Very Good), and language material experts 90%, in the quality aspect 92%, and in the language aspect 93.33% (Very Good). It was concluded that the development of a chain throwing game to improve softball overhand throws could be used by class XI students.